ACADEMIC FRAUD AND ARTIFICIAL INTELLIGENCE : A FRAUD DIAMOND THEORY PERSPECTIVE WITH MACHIAVELLIANISM AS MODERATOR - Muji Burrohman; Nur Aulia (LPPM STIE Muhammadiah Bandung, 2025)
This study aims to examine the influence of the Fraud Diamond dimensions—pressure, opportunity, rationalization, and capability—on academic fraud behavior, with the misuse of AI-generated content acting as a mediating variable. The research was conducted on students enrolled in the Corporate Financial Accounting study program at Politeknik Negeri Sambas. The sampling technique used was purposive sampling, targeting students who have taken or are currently taking the Professional and Business Ethics course. A total of 243 student responses were collected. This study employed a quantitative approach and utilized Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4 as the analytical tool. The findings show that pressure, capability, and rationalization significantly influence the misuse of AI-generated content, whereas opportunity does not. Additionally, pressure, opportunity, and capability have a direct effect on academic fraud behavior, while rationalization does not show a significant impact. The study also reveals that the misuse of AI-generated content does not mediate the relationship between the Fraud Diamond dimensions and academic fraud behavior. These results suggest that despite the availability of AI as a tool for academic misconduct, internal psychological and individual factors are more decisive in driving such behavior.